2009
DOI: 10.1042/cs20080325
|View full text |Cite
|
Sign up to set email alerts
|

QT interval prolongation and decreased heart rate variability in cirrhotic patients: relevance of hepatic venous pressure gradient and serum calcium

Abstract: A prolongation of QT interval has been shown in patients with cirrhosis and it is considered as part of the definition of the so-called 'cirrhotic cardiomyopathy'. The aim of the present study was to assess the determinants of QT interval prolongation in cirrhotic patients. Forty-eight male patients with different stages of liver disease were divided into three subgroups according to the Child-Pugh classification. All patients underwent a 24-h ECG Holter recording. The 24-h mean of QT intervals corrected for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
72
3
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 40 publications
(53 reference statements)
8
72
3
3
Order By: Relevance
“…The highest values of QT and QTc intervals were observed in class C (Child-Pugh) [4,[13][14][15][16]. Mozos et al confirmed these observations in a study involving 38 patients with cirrhosis; additionally they demonstrated a correlation with alcoholic cirrhosis etiology and the level serum uric acid [17].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The highest values of QT and QTc intervals were observed in class C (Child-Pugh) [4,[13][14][15][16]. Mozos et al confirmed these observations in a study involving 38 patients with cirrhosis; additionally they demonstrated a correlation with alcoholic cirrhosis etiology and the level serum uric acid [17].…”
Section: Discussionsupporting
confidence: 72%
“…Another study carried out on a Greek population revealed a correlation between the QT interval and the severity of cirrhosis, but not between the QT interval and cirrhosis etiology [18]. Genovesi et al demonstrated a significant correlation between the stage of cirrhosis according to the Child-Pugh classification, the hepatic venous pressure gradient (HVPG) and QT interval prolongation, which was more common in patients with alcoholic than viral cirrhosis [13]. QT interval prolongation independently predicts bleedinginduced mortality in patients with cirrhosis [19].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Bal and Thuluvath (15), a prolonged QTc was seen more commonly in patients with alcoholic cirrhosis (60%) compared to non-alcoholic cirrhosis (35%), and alcoholic cirrhosis was one of the independent predictors of QT interval prolongation. A study by Genovesi et al (16) suggests that the alcoholic etiology may indeed play a role in the prolongation of QT interval in cirrhotic patients, although the relatively small size of the population does not allow a precise definition of its contribution.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies (5,6,10,16) assessed the slope of the QT/RR relationship in long-term Holter recordings and investigated its meaning as a clinical characteristic. The majority of these studies investigated the relationship by means of linear regression between simultaneously measured QT and RR intervals; only infrequently was the linear regression applied to logarithmically transformed QT and RR data.…”
mentioning
confidence: 99%
“…Since the design of accurate individual QT rate corrections depends on accurate mathematical description of baseline QT/RR relationship (9), it has been proposed to fit different nonlinear models to the data of different individuals, which, in essence, means to classify the curvatures of the QT/RR patterns into several distinct categories (10,12). While this technology has been used successfully in studies of electrocardiographic drug effects (24, 25), it does not deal with the problem of the QT/RR curvature fully (26).…”
mentioning
confidence: 99%